The Effect of Round Table Technique On Students’ Ability In Writing Report Text of Nineth Grade Of SMP Pabaku Stabat In Academic Year 2018/2019 - Conny Conny; Riska Devita (STKIP Budidaya Binjai, 2019)
This research is conducted in order to improve students’ writing ability uing Round Table Technique at Nineth grade of SMP Pabaku Stabat. The study is concerning with experimental study which discussed the effect of round table technique on students’ ability in writing report text. It took place at SMP Pabaku Stabat. The subjects were the nineth grade students with the population of 132 students. 72 students were chosen as the sample and group into experimental and control group. Each group consisted of 36 students. The experimental group was taught with round table technique while the control one was taught without round table technique. A writing test was used to collect the data on the students’ writing ability. The data collected were analyzed by using t-test. The result of the data analysis showed that the t-observed was 7,24. It was higher that the value of t-table (tt) is 1,66 for 5% and 2,38 for 1%. This meant that the alternative hypothesis (Ha) was accepted. It can be concluded that there is effect of round table technique on students’ ability in writing report text of nineth grade of SMP Pabaku Stabat in academic year 2018/2019.